RESPON KUALITAS HASIL TANAMAN LABU ZUKINI TERHADAP FREKUENSI PEMBERIAN MOL KOHE KAMBING DAN JENIS PUPUK KANDANG - elsa rosalia larasati (AGRONISMA, 2022)
Zukini (Curcubita pepo L) is one of the vegetables that are in great demand by the people of Indonesia. This vegetable has a high nutritional value found in large fruits such as zucchini plants. The application of MOL in goat manure and types of manure can make it easier for plants to absorb nutrients in the soil and as a source of additional nutrients for plants. This study aims to determine the effect of the frequency of application of MOL in goat manure and the type of manure on the number of fruits, yield per hectare of plants, harvest index, and chlorophyll content in zucchini plants. This study used a factorial RAK (Randomized Block Design), the first factor was F1 : 1 time given moles in goat manure, F2: 2 times given moles in goat manure, F3: 3 times given moles in goat manure, F4: 4 times given moles in goat manure, factor second P1: chicken manure, P2: goat manure, P3: cow manure. Giving MOL once gave better yields on the yield of zucchini, which was 90.34 tons/ha. Keywords: zucchini plant, MOL kohe goat, manure